Museum politics : power plays at the exhibition - Luke, Timothy W. (University of Minnesota Press, 2002)
In this important volume, Timothy W. Luke explores museums' power to shape collective values and social understandings, and argues persuasively that museum exhibitions have a profound effect on the body politic.